Extension for Participation Operations of members Palm Oil Collaborative Farmers in Meuang Phang Nga District Phang Nga Province - ภักดี นายนพดล; ขลิบทอง จินดา; ตุ้มหิรัญ เฉลิมศักดิ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objectives of this research were to 1) study personal, social, and economic conditions of palm oil collaborative farming group members 2) study the significance and participation in the operations of members of oil palm collaborative farming group 3) compare the receiving and needs for extension in the participation of oil palm collaborative farming group members and 5) analyze the extension guidelines in the participation of oil palm collaborative farming group members. The population of this study was 135 oil palm farmers who were members of oil palm collaborative farming group in Mueang Phang Nga district, Phang Nga province who had registered with the department of agricultural extension ion in 2023. The sample size of 102 people was determined by using Taro Yamane formula with the error value of 0.05 through simple random sampling method. Interview forms were used in data collection. Data were then analyzed by using statistics such as frequency distribution, percentage, minimum value, maximum value, mean, standard deviation, T-test, and content analysis. The results of the research found that 1) most of the farmers (67.8%) were male with the average age of 59.64 years old. They were married, completed early secondary school education level, were member of collaborative farming group, had the average area for oil palm production of 9.96 Rai, owned their own land, earned the average income from oil palm production of 318,468.62 Baht/year, and used their personal fund in oil palm production. 2) Farmers had the level of significance at the highest level and had the level of participation at the lowest level. 3) Farmers faced with the problem in the participation as oil palm collaborative farming members at the highest level. 4) Farmers received the participation extension as oil palm collaborative farming members at the low level. They needed the participation extension as oil palm collaborative members at the highest level. 5) Extension guidelines in the participation in the operations of oil palm collaborative farming group included the aspect that the agricultural extension officers should have the key roles in providing knowledge, support, and participation extension of collaborative farming group member through personal media such as agricultural extension officers, community leaders, and model farmers along with publication media and electronic media with appropriate methods as per the targeted group such as visitation, demonstration, training, and field trips in order to motivate farmers to realize the significance of participation and to adopt it to increase the higher efficiency in the operation of the collaborative farming group.